STIM1 and Orai1 mediate CRAC channel activity and are essential for human glioblastoma invasion - Motiani, Rajender K.; Hyzinski-García, María C.; Zhang, Xuexin; Henkel, Matthew M.; Abdullaev, Iskandar F.; Kuo, Yu-Hung; Matrougui, Khalid; Mongin, Alexander A.; Trebak, Mohamed (Pflügers Archiv, 2013)
The Ca 2+ sensor stromal interacting molecule 1 (STIM1) and the Ca 2+ channel Orai1 mediate the ubiquitous store-operated Ca 2+ entry (SOCE) pathway activated by depletion of internal Ca 2+ stores and mediated through the highly Ca 2+ -selective, Ca 2+ release-activated Ca 2+ (CRAC) current. Furthermore, STIM1 and Orai1, along with Orai3, encode store-independent Ca 2+ currents regulated by either arachidonate or its metabolite, leukotriene C 4 . Orai channels are emerging as important contributors to numerous cell functions, including proliferation, migration, differentiation, and apoptosis. Recent studies suggest critical involvement of STIM/Orai proteins in controlling the development of several cancers, including malignancies of the breast, prostate, and cervix. Here, we quantitatively compared the magnitude of SOCE and the expression levels of STIM1 and Orai1 in non-malignant human primary astrocytes (HPA) and in primary human cell lines established from surgical samples of the brain tumor glioblastoma multiforme (GBM). Using Ca 2+ imaging, patch-clamp electrophysiology, pharmacological reagents, and gene silencing, we established that in GBM cells, SOCE and CRAC are mediated by STIM1 and Orai1. We further found that GBM cells show upregulation of SOCE and increased Orai1 levels compared to HPA. The functional significance of SOCE was evaluated by studying the effects of STIM1 and Orai1 knockdown on cell proliferation and invasion. Utilizing Matrigel assays, we demonstrated that in GBM, but not in HPA, downregulation of STIM1 and Orai1 caused a dramatic decrease in cell invasion. In contrast, the effects of STIM1 and Orai1 knockdown on GBM cell proliferation were marginal. Overall, these results demonstrate that STIM1 and Orai1 encode SOCE and CRAC currents and control invasion of GBM cells. Our work further supports the potential use of channels contributed by Orai isoforms as therapeutic targets in cancer.